Real-World Anticoagulatory Treatment After Transcatheter Aortic Valve Replacement: A Retrospective, Observational Study on 4,800 Patients - Hohmann, Christopher; Ludwig, Marion; Walker, Jochen; Wienemann, Hendrik; Baldus, Stephan; Pfister, Roman (Frontiers in Cardiovascular Medicine, 2021)
Background Transcatheter aortic valve replacement (TAVR) has developed to the therapy of choice for patients with symptomatic severe aortic stenosis who are unsuitable for surgical aortic valve replacement and elderly patients with intermediate or high operative risk. However, the optimal anticoagulatory treatment post-TAVR still remains a matter of debate. Aims This study sought to investigate current anticoagulatory treatment patterns and clinical outcome in patients undergoing TAVR. Methods In a retrospective study based on anonymized health claims data of approximately seven million Germans with statutory health insurance (InGef database), anticoagulatory treatment regimens were assessed using any drug prescription post discharge within the first 90 days after TAVR procedure. Clinical events between 30 days and 6 months were examined by treatment regime. Results The study population comprised 4,812 patients with TAVR between 2014 and 2018: 29.4 % received antiplatelet monotherapy, 17.8 % dual antiplatelet therapy, 17.4 % oral anticoagulation (OAC) plus antiplatelet therapy, 12.9 % OAC monotherapy, 2.2 % triple therapy and 19.2 % did not receive any anticoagulatory drugs. 64 % of patients with OAC received non vitamin-K antagonist oral anticoagulants (NOAC). Hence, 68 % of all patients were treated non adherent to current guidelines. 40 % of patients with OAC prior to TAVR did not have any OAC after TAVR. The adjusted risk of all-cause mortality was significantly increased in patients with OAC (HR 1.40, 95% CI 1.03-1.90, p = 0.03) and no anticoagulatory treatment (HR 3.95, 95% CI 2.95-5.27, p < 0.0001) when compared to antiplatelet monotherapy. Conclusions This large real-world data analysis demonstrates substantial deviations from guideline recommendations and treatment after TAVR. Considering relevant differences in clinical outcome across treatment groups, major effort is warranted to examine underlying causes and improve guideline adherence.